2021
DOI: 10.1186/s12876-021-01911-5
|View full text |Cite
|
Sign up to set email alerts
|

Mutation analysis of the ATP7B gene and genotype–phenotype correlation in Chinese patients with Wilson disease

Abstract: Aim To discover the novel ATP7B mutations in 103 southern Chinese patients with Wilson disease (WD), and to determine the spectrum and frequency of mutations in the ATP7B gene and genotype–phenotype correlation in a large-scale sample of Chinese WD patients. Methods One hundred three WD patients from 101 unrelated families in southern China were enrolled in this study. Genomic DNA was extracted from the peripheral blood. Direct sequencing of all 21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 50 publications
1
5
2
1
Order By: Relevance
“…The exons that were hotspots were examined in the 39 WD patients. The results showed that exons 8 and 18 harbored the highest percentage of mutations, which was not consistent with previous results that exons 8, 13 and 16 were the hotpot exons in the Chinese population ( Li et al, 2021 ). This result may be due to the differences between Han individuals and ethnic minorities.…”
Section: Resultscontrasting
confidence: 97%
See 2 more Smart Citations
“…The exons that were hotspots were examined in the 39 WD patients. The results showed that exons 8 and 18 harbored the highest percentage of mutations, which was not consistent with previous results that exons 8, 13 and 16 were the hotpot exons in the Chinese population ( Li et al, 2021 ). This result may be due to the differences between Han individuals and ethnic minorities.…”
Section: Resultscontrasting
confidence: 97%
“…The top five most common mutations in our study were c.2333G > T (p.R778L), c.2975C > T (p.P992L), c.2621C > T (p.A874V), c.3809A > G (p.N1270S) and c.2804C > T (p.T935M), which is not consistent with other reported studies (p.R778L, p.P992L, p.A874V, p.R919G and p.V1216M) ( Li et al, 2021 ). Mutation hotspots in ATP7B vary by geographic region, with a higher prevalence of specific mutations reported in certain populations ( Wallace and Dooley, 2020 ).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“… 28 , 29 Traditionally, the diagnosis of WD mainly depends on clinical manifestations and routine biochemical indexes, including hepatic copper content, 24‐hour elevated urinary copper, and decreased serum CP. 30 However, patients with mild symptoms may be misdiagnosed, resulting in delayed treatment. 20 Gene detection of ATP7B gene mutation may lead to reliable early diagnosis and treatment to prevent copper accumulation and tissue damage.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, no significant difference was detected in ceruloplasmin levels in WD patients with or without K–F rings ( 6 ). In addition, some studies observed lower serum ceruloplasmin levels in patients with R778L homozygous mutations than in patients without R778L mutations ( 21 ). Another study reported that low serum ceruloplasmin levels were associated with truncating mutations in the ATP7B gene ( 22 ).…”
Section: Discussionmentioning
confidence: 99%